Solusi Syar’i Terhadap Hubungan Mahram pada Keluarga Adopsi: Sharī‘ah Oriented Legal Approaches to Regulating Mahram Relations within Adoptive Families - Marbujang; Syahrial Dedi; Rifanto Bin Ridwan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
The question of mahram status in adoptive families constitutes a substantive normative challenge within Islamic family law, particularly when adoption is not supported by a Sharī‘ah-recognized mechanism capable of creating legally valid kinship ties. Although adoptive relationships frequently cultivate deep emotional attachment and social cohesion, such bonds do not, in themselves, establish mahram status. This distinction necessitates careful legal examination. This research therefore analyzes the doctrinal framework regulating mahram relations in adoptive contexts and formulates sharī‘ah-based responses suited to contemporary muslim societies. Using a normative legal research model, the study combines conceptual, comparative, and ushul fiqh approaches. Its primary sources consist of the Qur’an, hadith, classical fiqh literature, and recent scholarly publications. The analysis employs content analysis, comparative assessment of juristic opinions, and reasoning grounded in maqāṣid al-syarī‘ah. The findings affirm that mahram status arises solely through nasab, muṣāharah, or raḍā‘ah that fulfills established legal requirements. Moreover, juristic disagreement concerning the age limit of raḍā‘ah significantly shapes modern legal interpretations of adoption. Accordingly, the study advances a tiered sharī‘ah based framework prioritizing early childhood raḍā‘ah and contextual ijtihād grounded in maṣlaḥah and legal prudence.